CSC574 - Dynamic Web Application Development / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
The course introduces the students to web programming. It covers, among others, mark-up language, client-side scripting and server-side scripting.